2021
DOI: 10.1002/ppul.25539
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and intermittent administration of intravenous sildenafil in critically ill infants with pulmonary hypertension

Abstract: Intravenous (IV) sildenafil may be administered as a continuous infusion or intermittent bolus dosing in infants with pulmonary hypertension (PH). We aimed to compare these delivery methods.Methods: We retrospectively evaluated subjects less than 12 months old treated with IV sildenafil for PH. Vital signs, oxygen requirement, vasoactive-inotropic score (VIS), and echocardiogram results before and after sildenafil initiation, and the need for discontinuation due to side effects, were noted.Results: Forty-three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Our results illustrate, that intravenous sildena l treatment is associated with a signi cant and rapid reduction of the PH severity. This is in line with previous studies on infants with PPHN and neonates suffering from PH due to congenital lung disease or BPD-PH [15,19,30,31,33]. According to our results, the RVD improves signi cantly during the continuous sildena l infusion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results illustrate, that intravenous sildena l treatment is associated with a signi cant and rapid reduction of the PH severity. This is in line with previous studies on infants with PPHN and neonates suffering from PH due to congenital lung disease or BPD-PH [15,19,30,31,33]. According to our results, the RVD improves signi cantly during the continuous sildena l infusion.…”
Section: Discussionsupporting
confidence: 93%
“…In recent prospective trials intravenous sildena l treatment was evaluated in neonates with a gestational age >34 weeks , but data on intravenous sildena l in ELGAN and ELBW preterm infants <28 GA are still lacking [13,14]. Several studies analyzed oral sildena l treatment and only two recent studies were identi ed analyzing intravenous sildena l treatment including ELBW infants with PH [15,17,30,31]. In most of these infants PH was diagnosed secondary to the timepoint of BPD diagnosis (36 weeks of GA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent prospective trials intravenous sildenafil treatment was evaluated in neonates with a gestational age > 34 weeks, but data on intravenous sildenafil in ELGAN and VLBW preterm infants < 28 GA are still lacking 13 , 14 . Several studies analyzed oral sildenafil treatment and only two recent studies were identified analyzing intravenous sildenafil treatment including VLBW infants with PH 15 , 17 , 30 , 31 . In most of these infants PH was diagnosed secondary to the timepoint of BPD diagnosis (36 weeks of GA).…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil is available as intravenous (continuous and intermittent) and oral (sildenafil-citrate) form of administration. In recent years, several studies evaluated sildenafil as treatment for PH (BPD-PH, PPHN) in preterm and term infants in prospective trials 13 15 . The majority of the studies published to date and included in the Cochrane review of sildenafil treatment for PH (2017) were exclusively enrolling neonates with a GA > 34 weeks 16 .…”
Section: Introductionmentioning
confidence: 99%